2015
DOI: 10.1038/bjc.2015.218
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer and the risk of squamous cell carcinoma of oesophagus: a case–control study in Kashmir, India

Abstract: Background:Only a few studies have examined the association between family history of cancer (FHC) and the risk of oesophageal squamous cell carcinoma (ESCC) in high incidence areas of ESCC. We conducted a case–control study to evaluate the relationship between FHC and ESCC risk in Kashmir, India, with analysis of detailed epidemiological data and information on multiple gene polymorphisms.Methods:We collected detailed information on FHC and a number of socio-demographic and lifestyle factors, and also obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 62 publications
(90 reference statements)
2
11
0
Order By: Relevance
“…Familial aggregation of GC may be caused by shared environmental factors as well as common genetic backgrounds [7]. There are several reports showing the association between some genetic polymorphisms and GC or other cancer risks among individuals with a family history of cancers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Familial aggregation of GC may be caused by shared environmental factors as well as common genetic backgrounds [7]. There are several reports showing the association between some genetic polymorphisms and GC or other cancer risks among individuals with a family history of cancers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that polymorphisms of CYP2D6 imposed an increased risk of breast cancer and esophageal squamous cell carcinoma in those people with a family history of cancers. 43,44 Zienolddiny S et al found that CYP2D6 and CYP1B1 increased genetic susceptibility to NSCLC. 45 In addition, Lee JY et al showed that hydroxychloroquine metabolism was related to CYP2D6 rs1065852 polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies explore the prognostic value of family history of cancer to ESCC. Other studies have shown that family history of any cancer in first-degree relatives was one of the risk factor for ESCC (Bhat et al 2015;Gao et al 2009), and Chen et al proved that family history of EC was the risk factor of ESCC (Chen et al 2015). In addition, Jiang et al indicated that family history of EC was one of the independent prognostic factors for survival of ESCC (Yuequan et al 2010).…”
Section: Esccmentioning
confidence: 99%